Political Communication Strategy in Realizing Deliberative Democracy: A Study of @bijakmemilih.id on the Website and X (Twitter) During the 2024 Election - Saffa, Kirana Anindya; Aji, Muhammad Prakoso (LPPM Universitas Jambi, 2026)
The 2024 Indonesian General Election witnessed a severe deliberative degradation within the digital public sphere, heavily distorted by affective polarization, information disorder, and algorithmic bias across mainstream social media. This study evaluates the political communication strategy of the independent civic technology platform @bijakmemilih.id in mitigating this structural crisis and restructuring cyber-discourses for young voters. Drawing upon Jürgen Habermas’s theory of deliberative democracy and Andrew Chadwick’s hybrid media system framework, a qualitative case study design was employed. Methodological triangulation was operationalized by integrating netnographic observations, in-depth interviews with key platform initiators, communication experts, and users, along with computational text mining via RapidMiner on substantive replies from key X (formerly Twitter) threads. The results demonstrate that @bijakmemilih.id successfully orchestrated a two-tiered communication strategy, functionalizing platform X as a fast-paced horizontal distribution channel for agenda-setting, while maintaining the official website as a deeply anchored vertical data repository. Interactivity emerged as the absolute dominant indicator in public discourse (31.7%), successfully transforming passive youth consumption into proactive communicative action through debate propositions and structural recommendations. Inclusivity (25.9%) was strategically achieved by deploying issue-based interactive features that effectively deconstructed embedded partisan tribalism. Accessibility (21.7%) developed independently via organic digital word-of-mouth distribution channels. Although rationality (20.6%) registered the lowest quantitative frequency, it generated the highest substantive conversational weight, utilizing objective track records as a crucial cognitive literacy shield against the manipulation of cyber troops. This study concludes that non-partisan, data-driven civic tech initiatives can effectively facilitate a healthy, inclusive, and rational deliberative digital public sphere amidst heavily commercialized media ecosystems.